Can Social Media Influence Green Investment Decisions? A Moderated TPB-Based Study among Young Investors - Meita Dwi Cahyani; Denies Priantinah (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
This study investigates the influence of attitude, subjective norm, and perceived behavioral control on green investment intention among student investors, with social media usage as a moderating variable based on the Theory of Planned Behavior (TPB). A quantitative survey was conducted among 210 university students in Yogyakarta, Indonesia, who have previously invested or held capital market accounts. Data were collected through an online questionnaire and analyzed using SmartPLS. The findings reveal that attitude, subjective norm, and perceived behavioral control significantly and positively influence green investment intention. However, social media usage does not moderate the relationship between these three variables and green investment intention. This suggests that although students actively use social media, they do not consistently use it as a source of reliable or influential information for green investment decisions. Instead, entertainment and social interaction remain dominant motivations for social media usage.